2019
DOI: 10.48550/arxiv.1909.08832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalised Krein-Feller operators and gap diffusions via transformations of measure spaces

Abstract: We consider generalised Kreȋn-Feller operators ∆ ν,µ with respect to compactly supported Borel probability measures µ and ν under the natural restrictions supp(ν) ⊂ supp(µ) and µ atomless. We show that the solutions of the eigenvalue problem for ∆ ν,µ can be transferred to the corresponding problem for the classical Kreȋn-Feller operator ∆ ν,Λ = ∂ µ ∂ x with respect to the Lebesgue measure Λ via an isometric isomorphism of the underlying Banach spaces. In this way we reprove the spectral asymptotic on the eige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The spectral properties for the generalised case were studied in [Küc86], [Vol05] and [Fre05]. The connection between the generalised and the classical Kreȋn-Feller operator has been elaborated in [Kes+19]. In there, it has been shown that the spectral behaviour can be reduced to the classical Kreȋn-Feller operator by a straightforward transformation of measure spaces.…”
Section: Dirichlet Forms For the Generalised Kreȋn-feller Operatormentioning
confidence: 99%
“…The spectral properties for the generalised case were studied in [Küc86], [Vol05] and [Fre05]. The connection between the generalised and the classical Kreȋn-Feller operator has been elaborated in [Kes+19]. In there, it has been shown that the spectral behaviour can be reduced to the classical Kreȋn-Feller operator by a straightforward transformation of measure spaces.…”
Section: Dirichlet Forms For the Generalised Kreȋn-feller Operatormentioning
confidence: 99%